The study of technophobia among students in UiTM Kedah / Jasmin Ilyani Ahmad … [et al.] - Ahmad, Jasmin Ilyani; Ahmad, Erny Arniza (2010)
This study examined technological sophistication and the level of technophobia in UiTM Kedah from six different programs; Diploma Senireka Perindustrian, Diploma Pengurusan Perniagaan, Diploma Pentadbiran Awam, Diploma Perakaunan, Diploma Perbankan dan Diploma Pengurusan Maklumat. Technological sophistication was measured by the use of consumer technology (automated teller machine (ATM), microwave ovens, CD/DVD player, washing machine and mobile phone), university computing (computerized library system (Web OPAC and Web lnfoline), application program (word processor, spreadsheet and database) and computer ownership. Technophobia was assessed by instruments measuring anxiety, cognitions and attitudes toward computer technology. Result indicated that some programs shows high experience in using consumer technology and the respondents also shows less negative attitudes towards computer technology.